‘He moved then?’: The management of worry-indicative information requests in moderate and high-risk fetal ultrasounds - Frezza, Minéia; Ostermann, Ana Cristina (Calidoscópio, 2021)
This study analyzes video-recorded fetal ultrasound scans held in a moderate and high-risk pregnancy ward at a Brazilian public hospital. Informed by Multimodal Conversation Analysis (Mondada, 2018), it investigates the ethnomethods participants employ to manage worry-indicative concerns whose presentation is initiated by pregnant women during a medical exam that does not typically comprise a specific phase for that (Nishizaka, 2010, 2011b, 2014). The analysis shows that pregnant women orient to three environments to request worry-indicative information: (i) topic, (ii) image, and (iii) phase transition, tailoring the design of their requests to each particular environment. Our findings reveal that, despite previous studies claiming otherwise, pregnant women are highly agentive in finding optimal opportunities to raise their concerns and to mobilize health professionals to respond to them. The physicians performing the scans respond to those requests while dealing with the contingencies inherent to the context of fetal ultrasounds which have implications for the provision of information. The analysis reveals the interplay between the pregnant women’s ethnomethods of raising concerns where ‘normality’ is constantly at stake and the health professionals’ ethnomethods in attending to those demands while orchestrating the distinct semiotic resources involved in the multiactivity setting of ultrasound scans. Keywords: Multimodal Conversation Analysis; Fetal ultrasound scans; Information requests; Doctor-Patient Interaction; Health Communication.